Incidence and mortality trends of aspiration pneumonia in Parkinson's disease in the United States, 1979–2010. Issue 9 (September 2015) - Akbar, Umer; Dham, Bhavpreet; He, Ying; Hack, Nawaz; Wu, Samuel; Troche, Michelle; Tighe, Patrick; Nelson, Eugene; Friedman, Joseph H.; Okun, Michael S.
Abstract Introduction Careful examination of long-term analyses and trends is essential in understanding the medico-economic burden of this common complication. We sought to describe the long-term (32-year) trends of incidence and mortality in PD patients hospitalized with aspiration pneumonia (AsPNA). Methods Incidence and mortality of AsPNA in hospitalized PD versus non-PD patients was assessed by logistic regression analysis applied to a national database between the years 1979 and 2010. Covariates such as age-decennium, gender, year AsPNA occurred, and the interactions with PD diagnosis were investigated. Rate of AsPNA and mortality over the 32-years was trended and compared. Results AsPNA occurred in 3.6% of PD patients and 1.0% of non-PD patients. The average mortality for PD patients was less (17% vs. 22%). Long-term (32-year) trends revealed a nearly 10-fold increase in incidence of AsPNA in PD (0.4% in 1979, 4.9% in 2010), decreasing mortality overtime, higher likelihood in males, and increasing average age of AsPNA patients (steeper increase in PD). All p-values < 0.05. In regression analysis, each successive year had a slight increase in odds of AsPNA (OR 1.03 in PD, OR1.06 in non-PD). Conclusions Trends over 32 years revealed a 10-fold increase in AsPNA among PD and non-PD patients, and an associated decrease in mortality. Our data suggest that PD patients are living longer, have slightly more AsPNA, but a lower mortality than was seen in past decades. Further research should investigate the causes of AsPNA in PD, and also potential interventions to decrease its occurrence.